The transcriptional activity of hepatocyte nuclear factor 4 alpha is inhibited via phosphorylation by ERK1/2 - Vető, Borbála (2017)
Hepatocyte nuclear factor 4 alpha (HNF4α) nuclear receptor is a master regulator of hepatocyte development, nutrient transport and metabolism. HNF4α is regulated both at the transcriptional and post-transcriptional levels by different mechanisms. Several kinases (PKA, PKC, AMPK) were shown to phosphorylate and decrease the activity of HNF4α. Activation of the ERK1/2 signalling pathway, inducing proliferation and survival, inhibits the expression of HNF4α. However, based on our previous results we hypothesized that HNF4α is also regulated at the post-transcriptional level by ERK1/2. Here we show that ERK1/2 is capable of directly phosphorylating HNF4α in vitro at several phosphorylation sites including residues previously shown to be targeted by other kinases, as well. Furthermore, we also demonstrate that phosphorylation of HNF4α leads to a reduced trans-activational capacity of the nuclear receptor in luciferase reporter gene assay. We confirm the functional relevance of these findings by demonstrating with ChIP-qPCR experiments that 30-minute activation of ERK1/2 leads to reduced chromatin binding of HNF4α. Accordingly, we have observed decreasing but not disappearing binding of HNF4α to the target genes. In addition, 24-hour activation of the pathway further decreased HNF4α chromatin binding to specific loci in ChIP-qPCR experiments, which confirms the previous reports on the decreased expression of the HNF4a gene due to ERK1/2 activation. Our data suggest that the ERK1/2 pathway plays an important role in the regulation of HNF4α-dependent hepatic gene expression.